Imagine, we've colonized on the Moon! We're building huge Skyscrapers. And its easier in the Moon's low gravity than Earth's.
An engineer, at the top of a nearly finished Skyscraper, trying to join and tighten the last bolt of the building. But unfortunately he drops it!
Then what was the total time of flight, T for the bolt?
Details and Assumptions:
The height of the Skyscraper is H .
As there's no atmosphere in the Moon, air can't affect the motion of the bolt. So you can consider the bolt as a Freely Falling Body From Rest .
The height of each floor is .
The bolt took t seconds to cross the Ground Floor .
Acceleration due to gravity, g =
Moon's gravity is of Earth's.
......Hope you don't make a Spontaneous or Random choice......!!!
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let's analyze the Clues given:
The height of the Skyscraper is H . So you can consider the bolt as an object falling from height, H (and from Rest , of course).
The height of each floor is n 1 H . So height of the Ground Floor is the same!
The bolt took t seconds to cross the Ground Floor.
This Necessarily means that The bolt crossed n 1 H = n H in the last t seconds .
Now let's make some equations:
Assume, total time of flight= T The bolt crossed H distance in this time.
Assume,the acceleration due to gravity for Moon= g
So H = u t + 2 1 g T 2 → H = 2 1 g T 2
The bolt crossed H − n H = H ( 1 − n 1 ) distance in ( T − t ) seconds [Note this! You must have to understand it.] .
So, H ( 1 − n 1 ) = 2 1 g ( T − t ) 2 → H = 1 − n 1 2 1 g ( T − t ) 2
From the above two equation, let's do some little Algebra.
I will briefly describe every step, for easy understanding. You may shorten it as you need!
2 1 g T 2 = 1 − n 1 2 1 g ( T − t ) 2
→ 2 1 g T 2 = 2 1 ( n − 1 ) n g ( T − t ) 2
→ T 2 = ( n − 1 ) n ( T − t ) 2
→ T = n − 1 n ( T − t )
→ T ( n − 1 ) = n T − n t
→ T ( n − n − 1 ) = n t
→ T = n − n − 1 n t Yahoo! Its the answer!!!
You may notice that the equation doesn't contain g at all. Which means the time T is *g Independent * .
So no matter whether its Earth,Moon or not. The same equation is applicable for Mars, even for Comet 67-P! Maybe this equation will be helpful for our *Mars Colonization * "!!!
Photo Credit: Red Orbit